Effect of Different Teaching Techniques on the Acquisition of Grammatical Gender by Beginning German Second Language Learners. Issue 1 (25th May 2016) - Arzt, Jessica; Kost, Claudia
Abstract : The grammatical gender of German nouns continues to pose a challenge to second language learners. Following from a connectionist framework, this study explores the effect of two input enhancement techniques, color‐coding and gendered actors, on the learning of grammatical gender by beginning learners of German during a vocabulary acquisition activity. Results on an immediate post‐test show no significant differences between conditions. In the delayed post‐test, however, the control group experienced a significant decrease in accurate gender assignment of the target items, while the gendered actor group displayed a non‐significant loss in scores, and the color‐coding group actually displayed slightly better scores compared to the immediate post‐test. These results suggest that color‐coding might be the most effective, while also the least work‐intensive, technique for instructors to implement. Further pedagogical implications resulting from this study are discussed.